Effects of Different Stocking Densities on Snail Bellamya purificata Foot Muscle Nutritional Quality and Metabolic Function - Yingyue Lou; Rui Jia; Bing Li; Linjun Zhou; Jian Zhu; Yiran Hou (Animals)
Snail Bellamya purificata is not only useful for bioremediation, purifying aquaculture environments, but it is also a commercially valuable and nutritionally rich aquatic product. To analyze the effect of various stocking densities on the muscle nutritional quality and metabolic functions of B. purificata. The transcriptome and metabolome were analyzed and set up three different density groups—low (LD, 234.38 g/m2), medium (MD, 468.75 g/m2), and high (HD, 937.5 g/m2). The results of the study showed that the weight gain (WG) and specific growth rate (SGR) of B. purificata in the MD and HD groups were significantly lower compared to the LD group. High stocking density significantly reduced the oleic acid (C18:1n9c), linoleic acid (C18:2n6c), alpha-linolenic acid (C18:3n3), eicosadienoic acid (C20:2), erucic acid (C22:1n9), docosahexaenoic acid (DHA, C22:6n3), and lignoceric acid (C24:0) levels within snail foot muscle. Most of the identified differentially expressed genes (DEGs) were categorized as Signal transduction, according to the Kyoto Encyclopedia of Genes and Genomes (KEGG); these genes were categorized into Transport and catabolism, Endocrine system, and Immune system. A total of 11 upregulated DEGs and 19 downregulated DEGs were identified and confirmed to be associated with density stress. The identified metabolites were mainly enriched in the Metabolism category, with 620 differential metabolites identified in positive ion (POS) mode and 265 differential metabolites identified in the negative ion (NEG) mode among different stocking density groups. The differential metabolites affected by stocking density were primarily amino acids, nucleic acids, vitamins, and lipid metabolites. There were 8 upregulated differential metabolites and 14 downregulated differential metabolites identified and confirmed to be associated with density stress. These findings elucidated the response mechanisms of B. purificata to adverse stocking density conditions and provide data and a theoretical basis for selecting appropriate stocking densities for B. purificata.